Hole and electron doping of topochemically reduced Ni(I)/Ru(II) insulating ferromagnetic oxides - Xu, Z; Jin, L; Backhaus, J-K; Green, F; Hayward, MA (American Chemical Society, 2021)
LaxSr2–xNiRuO6, LaxSr4–xNiRuO8, and LaxSr3–xNiRuO7 are, respectively, the n = ∞, 1, and 2 members of the (Lax/2Sr1–(x/2))nSr(Ni0.5Ru0.5)nO3n+1 compositional series. Reaction with CaH2, in the case of the LaxSr2–xNiRuO6 perovskite phases, or Zr oxygen getters in the case of the LaxSr4–xNiRuO8 and LaxSr3–xNiRuO7 Ruddlesden–Popper phases, yields the corresponding topochemically reduced (Lax/2Sr1–(x/2))nSr(Ni0.5Ru0.5)nO3n–1 compounds (LaxSr2–xNiRuO4, LaxSr4–xNiRuO6, and LaxSr3–xNiRuO5), which contain Ni and Ru cations in square-planar coordination sites. The x = 1 members of each series (LaSrNiRuO4, LaSr3NiRuO6, and LaSr2NiRuO5) exhibit insulating ferromagnetic behavior at low temperature, attributable to exchange couplings between the Ni1+ and Ru2+ centers they contain. Increasing the La3+ concentration (x > 1) leads to a reduction of some of the Ru2+ centers to Ru1+ centers and a suppression of the ferromagnetic state (lower Tc, reduced saturated ferromagnet moment). In contrast, increasing the Sr2+ concentration (x < 1) oxidizes some of the Ru2+ centers to Ru3+ centers and enhances the ferromagnetic coupling (increased Tc, increased saturated ferromagnet moment) for the n = ∞ and n = 2 samples but appears to have no influence on the magnetic ordering temperature of the n = 1 samples. The magnetic couplings and influence of doping are discussed on the basis of superexchange and direct exchange couplings between the square-planar Ni and Ru centers.